PRODUKSI GUM ARABIC BALURAN SEBAGAI PENDUKUNG PENGEMBANGAN WISATA KAMPUNG BANTENG DI KARANG TEKOK SEBAGAI WILAYAH PENYANGGA TN BALURAN - Kusumah, Maulana S.; Wiyono, Hidayat Teguh; Subekti, Agus; Muzakhar, Kahar; Winarsa, Rudju (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
This article is the result of PPDM (Mitra Desa Service Program) about Baluran bos javanicus (Banteng) village tourism. Development of bull village tourism is an effort to solve the problem of wild grazing in Bunaken National Park. In the event of Banteng Village Tourism, it is necessary to support tourism, namely creative industries, agro-tourism, and NTFP production (non-timber forest products). One of the NTFPs that is relied upon is Arabic gum. Currently, cattle breeders in the banteng village area have been able to produce Arabic gum as a result of the introduction of tapping technology by the 2019 PPDM team. The dedication method is in the form of dissemination and field practice. Three groups representing breeders were trained to tap acacia gum through a drilling method combined with ethephon induction as GIS. One week after application, the group begins harvesting gum and submits the results to the group leader. Then the group leader sends the results to the Cooperative in Pondok Pesantren Assalam, Sumberanyar, Banyuputih Situbondo. The amount of Baluran Arabic gum that was collected by the group for three months reached 143.9 kg. This service activity concludes that the strength in producing Baluran Arabic gum is significant in improving the welfare of breeders in supporting the maintenance and retention of a Banteng.